HUBUNGAN TINGKAT PENGETAHUAN IBU NIFAS TENTANG INFEKSI DENGAN PERAWATAN LUKA PERINEUM DI RS PKU MUHAMMADIYAH DELANGGU - Jati, Fristia Yuanita Efendi; , STIKES PKU Muhammadiyah Surakarta, Rizka Fatmawati (Jurnal Kebidanan, 2014)
ABSTRACT One of the causes of postpartum infection, because of the injury to the former birth canal injury, injury to the perineum episiotomy due to uterine rupture or laceration of an area that is susceptible to infection. Objective to determine the level of knowledge about postpartum maternal infection with perineal wound care at PKU Muhammadiyah Hospital Delanggu. This study uses observational analytic cross sectional approach. The total number of population of 31 people, total sampling using sampling techniques, namely on 31 new mothers who gave birth in hospital PKU Delanggu Muhammadiyah. Means of data collection using questionnaires. Data analysis using chi square analysis The results of statistical tests found an association between postpartum maternal knowledge about infection with perineal wound care chi-square value of 10.084 indicated by the calculated value of X2> X2 table (10.084> 9.488) and calculate P values ​​<P Table (0.039 <0.05 ). There is a relationship between postpartum maternal knowledge about infection with perineal wound care at PKU Muhammadiyah Hospital Delanggu Keywords : Knowledge Capital Ruling On Infection, Wound Care perineum